2009
DOI: 10.1371/journal.pone.0007746
|View full text |Cite
|
Sign up to set email alerts
|

Targeted KRAS Mutation Assessment on Patient Tumor Histologic Material in Real Time Diagnostics

Abstract: BackgroundTesting for tumor specific mutations on routine formalin-fixed paraffin-embedded (FFPE) tissues may predict response to treatment in Medical Oncology and has already entered diagnostics, with KRAS mutation assessment as a paradigm. The highly sensitive real time PCR (Q-PCR) methods developed for this purpose are usually standardized under optimal template conditions. In routine diagnostics, however, suboptimal templates pose the challenge. Herein, we addressed the applicability of sequencing and two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
64
0
4

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 54 publications
5
64
0
4
Order By: Relevance
“…8 Finally, real-time allelic discrimination could also be a good alternative for direct sequencing because of the rapidity and high sensitivity of the technique; however, the difficulty of multiplexing and the similarity between the probes lead to higher DNA input and a high risk of decreased specificity due to cross reactivity of the different probes. 10 When considering all aspects, we conclude that for colon cancer diagnostics, in which sensitivity is generally not an issue, and when capillary electrophoresis facilities are already available, SNaPshot can be as valuable as direct sequencing. Workflow, time to results, hands-on time, and costs do not vary much between both techniques.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…8 Finally, real-time allelic discrimination could also be a good alternative for direct sequencing because of the rapidity and high sensitivity of the technique; however, the difficulty of multiplexing and the similarity between the probes lead to higher DNA input and a high risk of decreased specificity due to cross reactivity of the different probes. 10 When considering all aspects, we conclude that for colon cancer diagnostics, in which sensitivity is generally not an issue, and when capillary electrophoresis facilities are already available, SNaPshot can be as valuable as direct sequencing. Workflow, time to results, hands-on time, and costs do not vary much between both techniques.…”
Section: Discussionmentioning
confidence: 88%
“…To reliably test a sample, at least 20% to 30% of tumor cells are needed. To date, there are several alternative assays available for (KRAS) mutation detection, including "homebrew" assays, such as high-resolution melting curve analysis (HRM), 7 pyrosequencing, 8 single nucleotide primer extension assay, 9 and allele-specific real-time PCR, 10 and commercially available assays, such as reverse hybridization test KRAS StripAssay (Vienna Labs, Vienna, Austria) 11 and real-time PCR-based TheraScreen (Roche Diagnostics, Almere, the Netherlands); all these assays greatly differ in sensitivity, specificity, DNA input, time to results, hands-on time, flexibility, workload, and costs. The single nucleotide primer extension (SNaPshot) assay is a home-brew, flexible assay, which might be easily extendable to other biomarkers, whereas from the commercially available assays, the KRAS StripAssay claims to be fast and very sensitive.…”
mentioning
confidence: 99%
“…The sensitivity of the TheraScreen ® kit is reported by the company to be 1% depending on the total amount of DNA used (http://www.dxsdiagnostics.com). However, it has been reported that only a minority of diagnostic samples derived from FFPE tissues can be analyzed at this level of sensitivity (Kotoula, et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…In molecular endocrinology, these approaches are of enormous importance for the diagnosis of inherited disease-causing mutations and/or somatic mutations. Therefore, the adequate isolation of nucleic acids from peripheral blood, fine-needle aspiration (FNA) cells in stained slides, and fresh and formalin-fixed/paraffinembedded (FFPE) tissues is crucial to ensure the success of these techniques, posing a challenge for routine DNA extraction protocols, especially when blood samples and FFPE tissues have been stored for long period, and when no other samples can be collected from patients lost to follow-up (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, obtaining DNA and RNA from FFPE samples and stained slides is always a challenge because fixation, embedding, staining, and extraction methods generally inhibit nucleic acid retrieval from the samples (3). On the other hand, although formalin fixation may degrade nucleic acids, it also deactivates nucleases and, thus, has a stabilizing effect (3).…”
Section: Introductionmentioning
confidence: 99%